Existence of Traditional Markets to Modern Markets in Coastal Areas - Eka Hendi Andriansyah; Eka Indah Nurlaili; M. Riadhos Solichin; Naning Eko Noviana (Universitas Muhammadiyah Prof. DR HAMKA., 2021)
This study aims to determine whether sales and location of modern markets affect sales in traditional markets. This study uses a quantitative approach, with data collection techniques using questionnaires, interviews, and documentation. The data analysis technique was using a multiple linear regression model using a level of 0.05 (5%) with the classical assumption test. Statistical results show that the Sales variable has an at-count value of 2,049 with an at-table value of 1,666. In the location variable, the t-count value is 3.146 with an at-table value of 1.666 at the 0.02 level. In conclusion, there is an influence between the level of modern market sales on sales turnover in traditional markets. The three dominant indicators are the income level of the community, products, and customers with a significant decline. the influence of modern market location on sales turnover in traditional markets. This condition is dominated by three indicators, including market traffic, availability of parking spaces, and market environment. Traditional markets can survive by increasing their advantages in terms of customer satisfaction through improved service in a family manner, lower product prices, product freshness, and infrastructure through which can be facilitated by the local government.